Factors That Affect Cost and Time Using Earned Value In Development Projects - Titik Nurkaruniati; Budi Witjaksana; Hanie Teki Tjendani (Asian Journal of Social and Humanities, 2024)
Effective project management is the key to success in constructing the boarding school of SMA Muhammadiyah 3 Tulangan. Despite facing various challenges such as design changes, inclement weather, and limited workforce resources, the project is monitored using the Earned Value Method. Analysis of BCWS, BCWP, ACWP, SV, CV, SPI, and CPI indicates initial delays and budget overruns, but significant improvement later on. Despite weekly cost variations, the project remains financially manageable. The conclusion shows time delays but cost performance is under control. This underscores the importance of project performance evaluation and the use of the Earned Value Method in construction projects.